(untitled) (Experimental biology, 2015)
The biosorption of Co and Ni by actinomycetes Streptomyces sp. 450 and Streptomyces sp.15 have been studied. It is shown that pretreatment of biomass with various substances led to various degrees of metal sorption by actinomycetes. Sorption of cobalt from the solution by biomass killed by heating at 80 °C decreased for Streptomyces sp. 450 to 36%, for Streptomyces sp.15 to 42%. Biosorption of nickel by Streptomyces sp. 450 and Streptomyces sp.15 also decreased and was 37 and 28% respectively. Significant decrease in biosorption of cobalt and nickel was observed for the biomass of both actinomycetes treated with hydrochloric acid. Processing of microbial biomass by sodium dodecyl sulfate (SDS) and by the solution of methanol-chloroform also led to decrease in sorption capacity of actinomycetes. The best effect was observed after processing of the biomass of Streptomyces by ethanol. In this case, cobalt biosorption by biomass of Streptomyces sp. 450 increased up to 26%, Streptomyces sp.15 up to 34%, and Ni up to 17 and 24%, respectively, comparing with control.